Erratum: Korelasi Antara Kelincahan Dengan Topspin Tenis Meja Atlet Kota Kendari - Rahedin Suwo (JUARA : Jurnal Olahraga, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v5i1.770 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article